2020
DOI: 10.1080/15332985.2020.1837333
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism, mental health, and well-being in the lesbian, gay and bisexual community

Abstract: Volunteerism plays a vital role in connecting individuals with various communities to provide numerous forms of altruistic service across the US. However, little is known about the numbers of lesbian, gay, bisexual, transgender/gender diverse and queer+ (LGBTQ+) people who engage in volunteer roles and community engagement activities, and the impact this may have upon their well-being and mental health. This secondary analysis of lesbian, gay, and bisexual (LGB) individuals (N = 71, weighted) from the 2018 Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Finally, these results suggest that SMM, particularly those in states with unsupportive LGBTQ+ policies may benefit from social programming that promotes civic engagement, increases community connectedness, and provides opportunities to engage in relationships. Community civic participation has been found to predict empowerment directly (Wagaman, 2016) and indirectly via social justice orientation (Lardier et al, 2023) among LGBTQ+ youth, and among Lesbian, gay, and bisexual adults, volunteerism has been associated with improved mental health (Gates & Dentato, 2020). Given that over 400 anti-LGBTQ+ bills have been introduced by state legislatures so far this year (American Civil Liberties Union, 2023), community-based organizations working with this population might consider programs that contribute to sociopolitical engagement, potentially improving overall mental health as well.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, these results suggest that SMM, particularly those in states with unsupportive LGBTQ+ policies may benefit from social programming that promotes civic engagement, increases community connectedness, and provides opportunities to engage in relationships. Community civic participation has been found to predict empowerment directly (Wagaman, 2016) and indirectly via social justice orientation (Lardier et al, 2023) among LGBTQ+ youth, and among Lesbian, gay, and bisexual adults, volunteerism has been associated with improved mental health (Gates & Dentato, 2020). Given that over 400 anti-LGBTQ+ bills have been introduced by state legislatures so far this year (American Civil Liberties Union, 2023), community-based organizations working with this population might consider programs that contribute to sociopolitical engagement, potentially improving overall mental health as well.…”
Section: Discussionmentioning
confidence: 99%
“…de Wit et al, 2022), older gay men and lesbians who volunteered had higher levels of selfreported mental health than those who did not, and gay men reported lower levels of psychological distress and higher levels of social support. Similarly, Gates and Dentato (2020) analyzed a small sample of…”
Section: Lgbtq Volunteeringmentioning
confidence: 99%
“…Empirical studies found that volunteering participation might be helpful in improving the physical and psychological health of disabled people (Binder & Freytag, 2013;Borgonovi, 2008) as well as other marginalized or isolated groups, such as older adults (e.g., Jiang et al, 2020;Russell et al, 2019), LGBTQ+ individuals (Gates & Dentato, 2020), and the homeless (Morton & Cunning-Williams, 2009). Studies highlighted that volunteering-defined as "the act of freely doing something without remuneration that is intended to improve others' quality of life directly or indirectly, with the recipient being outside one's own household" (Cnaan & Park, 2016, p. 24)-may improve the mental health of individuals with disabilities because it makes the volunteers feel that they are physically and mentally capable of playing meaningful roles in the community (Drucker, 2006).…”
Section: Positive and Negative Effect Of Volunteering On Well-beingmentioning
confidence: 99%